Virtual non-compliance with Omega-3 treatment results in null effects: The RANGER study. (August 2021) - Harris, William S.; Johnston, Daniel T.
Highlights: ISSFAL recommends that Omega-3 blood levels be reported in treatment studies. A recent study found no effect of Omega-3 on cognitive function in soldiers. Blood tests showed that the lack of effect was due to significant non-compliance. Studies that don't give a treatment should not expect to find an effect. Abstract: A recent paper reported that 14 weeks of treatment with 2100 mg of EPA+DHA from krill oil had no effect on cognitive function in US Army Ranger trainees. Although the authors stated that poor compliance "may have contributed to a failure to detect a response, " no indication of exactly how poor the compliance was is given. We have therefore calculated, based on their reported blood EPA+DHA levels and published equations predicting how a given dose of EPA+DHA should affect erythrocyte EPA+DHA levels (i.e., the Omega-3 Index), that the effective compliance was actually <3%. This study underscores the importance of adhering to ISSFAL recommendations that baseline and end of study blood Omega-3 levels always be reported in intervention studies. In this case the observed changes in blood levels are critical for interpreting the findings: there was no effect because there was essentially no intervention.